Cross-sectional examination of physical and social contexts of episodes of eating and drinking in a national sample of US adults. Issue 12 (15th January 2014) - Oh, April; Erinosho, Temitope; Dunton, Genevieve; M Perna, Frank; Berrigan, David
Abstract Objective The current study characterizes associations between physical and social contexts of self-reported primary episodes of eating/drinking and sociodemographic and obesity-related variables in US adults. Design Multinomial logistic regression was used to analyse a nationally representative sample of adults from the 2006–2008 American Time Use Survey. Models identifying physical (where) and social (whom) contexts of primary eating/drinking episodes at the population level, controlling for demographic characteristics, weight status and time of eating, were conducted. Setting USA. Subjects A nationally representative sample of US adults (n 21 315). Results Eating/drinking with immediate family was positively associated with age (OR = 1·15 (95 % CI 1·04, 1·27) to 1·23 (95 % CI 1·09, 1·39)), education level (OR = 1·16 (95 % CI 1·03, 1·30) to 1·36 (95 % CI 1·21, 1·54)), obesity (OR = 1·13 (95 % CI 1·04, 1·22)), children in the household (OR = 3·39 (95 % CI 3·14, 3·66)) and time of day (OR = 1·70 (95 % CI 1·39, 2·07) to 5·73 (95 % CI 4·70, 6·99)). Eating in the workplace was negatively associated with female gender (OR = 0·65 (95 % CI 0·60, 0·70)) and children in the household (OR = 0·90 (95 % CI 0·83, 0·98)), while positively associated with non-white status (OR = 1·14 (95 % CI 1·01, 1·29) to 1·47 (95 % CI 1·32, 1·65)) and time of day (OR = 0·25 (95 % CI 0·28, 0·30) to 5·65 (95 % CI 4·66, 6·85)). Women (OR = 0·80 (95 % CI 0·74, 0·86)), those aged >34 years (OR = 0·48 (95 % CI 0·43, 0·54) to 0·83 (95 % CI 0·74, 0·93)) and respondents with children (OR = 0·69 (95 % CI 0·63, 0·75)) were less likely to eat in a restaurant/bar/retail than at home. Overweight and obese respondents had a greater odds of reporting an episode of eating in social situations v. alone (e.g. immediate family and extended family; OR = 1·13 (95 % CI 1·04, 1·22)) and episodes occurring in restaurant/bar/retail locations (OR = 1·12 (95 % CI 1·03, 1·23) to 1·14 (95 % CI 1·05, 1·24)). Conclusions Findings underscore the multidimensional nature of describing eating/drinking episodes. Social and physical contexts for eating/drinking and their demographic correlates suggest opportunities for tailoring interventions related to diet and may inform intervention targeting and scope.